Yarn-electrospun PVDF-HFP/CNC smart textiles for self-powered sensor in wearable electronics - Chen, Jiawei; Mahajan, Subhamoy; Gupta, Manisha; Ayranci, Cagri; Tang, Tian (Energy conversion and management. X, 2025)
[Display omitted] •PVDF-HFP/CNC composite nanofiber yarns were produced by yarn electrospinning.•CNC improved β phase content, piezoelectric, and mechanical properties of PVDF-HFP.•PVDF-HFP/CNC smart textile device output 21.2 V under compression of 20 N.•The device was integrated with touchscreen glove as a real-time motion sensor. The advancement of portable or wearable electronics has promoted research into flexible power sources that can be integrated seamlessly into devices. Wearable electronics, such as fitness tracking device, smart clothing, and medical sensors, require power sources that not only generate energy but also adapt to dynamic environments. To address such demand, we produced a self-powered device composed of electrospun PVDF-HFP/cellulose nanocrystal (CNC) composite yarns, which serve both as a flexible power source converting mechanical energy to electrical output and as a sensor providing real-time motion monitoring. As an example of its application, the self-powered device was integrated with touchscreen gloves to explore its functionality. Our results showed that CNC promoted β phase formation in PVDF-HFP, improving its piezoelectric and mechanical properties. The maximum voltage output obtained from the PVDF-HFP/CNC self-powered device was 21.2 V under compressive loads of 20 N at 0.5 Hz. The touchscreen glove integrated with the device offered good sensing performance to detect finger motions, such as single- and double-click or dragging even under sub-zero temperatures. The success of developing such sensor-integrated touchscreen gloves paves new avenues for human-technology interactions, highlights the dual functionality of these yarns as power sources and sensors, and represents a milestone in broadening the applications of wearable technologies.